Adsorption, isotherms and kinetics characteristics of solid state Mg exchanged bentonite for removal of methylene blue - Ahdieh Bavi; Mohammad Ghorbanpour; Mohammed Jaafar Ali Alatabe (Journal of Water and Environmental Nanotechnology)
This study investigated the removal of methylene blue dye from aqueous solutions using Mg solid state exchanged bentonite. Parent bentonite and magnesium exchanged bentonite were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), Brunauer Emmett Teller (BET), Energy dispersive X-ray spectroscopy (EDX), and Fourier transform infrared spectroscopy (FTIR). The parent bentonite showed the lowest removal efficiency (40.3%) and prepared magnesium exchanged bentonite for 10 min showed the highest removal efficiency (54.8%). Thus, dye absorption by modified bentonite increased compared to parent bentonite. After its modification by the ion exchange method, the specific surface was changed from 44.5 to 56.05 M2/g. EDX results indicate that the cation exchange process has been completed successfully. Ion exchange causes some minor changes in bentonite morphology and crystallinity. The best conditions for removing methylene blue using magnesium exchanged bentonite was pH 10, adsorbent dosage 0.05 mg/liter, initial concentration of solution 100 mg per liter, and contact time of 120 minutes with a Removal efficiency of 96.67. The Langmuir isotherm had a better correlation coefficient than the Freundlich adsorption model, which indicated the homogeneous surface of the adsorbent.